2015
DOI: 10.1186/s12943-015-0314-4
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA PCGEM1 is regulated by androgen receptor activity in vivo

Abstract: BackgroundLong non-coding RNAs (lncRNAs) can orchestrate oncogenic or tumor-suppressive functions in cancer biology. Accordingly, PCGEM1 and PRNCR1 were implicated in progression of prostate cancer (PCa) as transcriptional co-regulators of the androgen receptor (AR). However, these findings were recently refuted asserting that neither gene physically binds to the AR. Despite evidence for differing AR transcriptional programs in vivo and in vitro, studies investigating AR-regulation of these genes hitherto have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 28 publications
2
63
1
Order By: Relevance
“…EMT is an important step in metastasis, during which epithelial cells are transformed into mesenchymal cells under specific physiological and pathological conditions 30,31. MMP9 is frequently observed in prostate cancer progression,32,33 and the upregulated expression of MMP9 is usually correlated with the occurrence of metastasis or local progression of cancer 16. Studies have found that lncRNA promotes cancer metastasis by regulating the EMT process 34,35.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is an important step in metastasis, during which epithelial cells are transformed into mesenchymal cells under specific physiological and pathological conditions 30,31. MMP9 is frequently observed in prostate cancer progression,32,33 and the upregulated expression of MMP9 is usually correlated with the occurrence of metastasis or local progression of cancer 16. Studies have found that lncRNA promotes cancer metastasis by regulating the EMT process 34,35.…”
Section: Discussionmentioning
confidence: 99%
“…For the highly migrating DU145 cell line, pictures were taken till full “healing” of the NC‐treated cells (20 h). Cell fractionation and dihydrotestosterone (DHT) treatment of LNCaP cells have been previously described (Parolia et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Although the involvement of PCGEM1 in PC was widely reported, the role of PCGEM1 in PC is still controversial. For example, androgen deprivation is able to induce PCGEM1 and causes its accumulation in nuclear speckles 17 , while this was not the case in another study which revealed that PCGEM1 was stimulated by androgen and downregulated by castration in xenograft models 16 . Similarly, PCGEM1 along with PRNCR1 can impact AR signalling through interaction with AR to promote castration resistance 18 , however, this is not supported by a comprehensive analysis of RNA-sequencing data 19 .…”
Section: Discussionmentioning
confidence: 95%
“…PCGEM1 overexpression in LNCaP cells results in delayed induction of p53 and p21 induced by doxorubicin, which could therefore inhibit cell apoptosis 15 . Besides, PCGEM1 is an in vivo androgenregulated transcript with potential nuclear and/or cytoplasmic function 16 . Although the involvement of PCGEM1 in PC was widely reported, the role of PCGEM1 in PC is still controversial.…”
Section: Discussionmentioning
confidence: 99%